The role of bioactive lipids and lipid binding proteins in skeletal muscle - Mohd Noor, Mohd Fadly (2019)
Obesity and diabetes mellitus have been identified as major worldwide health problems. There is a growing body of evidence which suggests lipid signalling molecules including fatty acids, endocannabinoids and fatty acid amides may play a role in the development of obesity and insulin resistance. Much of the current research has focused upon the synthesis and release of such molecules by adipose tissue and their effects upon the endocrine system. Interestingly, cannabinoid (CB) receptors and other endocannabinoid components are also found to be expressed in human and animal skeletal muscle cells. However, there is minimal information regarding the role of these fatty acid derivatives in skeletal muscle and the lack of these data represents a significant gap in our knowledge. The aims of this thesis were to investigate the effects of cannabinoid receptor CB1 modulation upon insulin-stimulated glucose uptake and its effects upon regulation of selected genes expression in primary skeletal muscle myotubes. In addition, we would like to investigate the synthesis and secretion of Lipocalin 2 (LCN2), a type of lipid binding protein as a novel myokine.